Long-Term Effects of Peripubertal Binge EtOH Exposure on Hippocampal microRNA Expression in the Rat - Prins, Sarah A. (Public Library of Science, 2014)
Adolescent binge alcohol abuse induces long-term changes in gene expression, which impacts the physiological stress response and memory formation, two functions mediated in part by the ventral (VH) and dorsal (DH) hippocampus. microRNAs (miRs) are small RNAs that play an important role in gene regulation and are potential mediators of long-term changes in gene expression. Two genes important for regulating hippocampal functions include brain-derived neurotrophic factor (BDNF) and sirtuin-1 (SIRT1), which we identified as putative gene targets of miR-10a-5p, miR-26a, miR-103, miR-495. The purpose of this study was to quantify miR-10a-5p, miR-26a, miR-103, miR-495 expression levels in the dorsal and ventral hippocampus of male Wistar rats during normal pubertal development and then assess the effects of repeated binge-EtOH exposure. In addition, we measured the effects of binge EtOH-exposure on hippocampal Drosha and Dicer mRNA levels, as well as the putative miR target genes, BDNF and SIRT1. Overall, mid/peri-pubertal binge EtOH exposure altered the normal expression patterns of all miRs tested in an age- and brain region-dependent manner and this effect persisted for up to 30 days post-EtOH exposure. Moreover, our data revealed that mid/peri-pubertal binge EtOH exposure significantly affected miR biosynthetic processing enzymes, Drosha and Dicer. Finally, EtOH-induced significant changes in the expression of a subset of miRs, which correlated with changes in the expression of their predicted target genes. Taken together, these data demonstrate that EtOH exposure during pubertal development has long-term effects on miRNA expression in the rat hippocampus.